2013
DOI: 10.5152/kd.2012.20
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Results of Urine Cultures and Approaches to Empirical Antibiotic Treatment of Community-Acquired Urinary Tract Infections in Elderly Patients

Abstract: Üriner sistem infeksiyonu yaşlılarda en sık görülen bakteriyel infeksiyonlardandır. Bu çalışmada, hastanemizde yaşlı hastalarda toplumdan kazanılmış üriner sistem infeksiyonlarında ilk seçenek olarak önerilen antibiyotiklere karşı direnç oranlarının saptanması ve ampirik antibiyotik tedavisi için yol gösterici sonuçlar elde edilmesi amaçlanmıştır. Yöntemler: Bu çalışma, Mart 2010 ile Mart 2012 tarihleri arasında hastanemizde takip ve tedavi edilen 65 yaş ve üzeri hastaların verilerinin retrospektif olarak değe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 3 publications
2
11
0
Order By: Relevance
“…Intensive use of antibiotics has created the problem of antibiotic resistance in this disease group and made the treatment of uncomplicated cases difficult as well. In Turkey, the most commonly preferred antibiotics for the treatment of urinary tract infection are cotrimoxazole, ciprofloxacin, and cephalosporins (19,25). However, studies published from Turkey have shown that we have reached the end of the road in the use of these antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Intensive use of antibiotics has created the problem of antibiotic resistance in this disease group and made the treatment of uncomplicated cases difficult as well. In Turkey, the most commonly preferred antibiotics for the treatment of urinary tract infection are cotrimoxazole, ciprofloxacin, and cephalosporins (19,25). However, studies published from Turkey have shown that we have reached the end of the road in the use of these antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the most frequently isolated pathogen was E. coli (58 %). Similarly, Ulug et al [6] reported the rate of E. coli isolated as a causative agent of UTI was 64% in 401 elderly patients. This rate was 32% in elderly patients admitted to the emergency room and diagnosed with UTI in the study by Ginde et al [12], 69% in elderly patients who resided in nursing homes in the study by Sundwall et al [11], and 54% in the study by Das et al [13].…”
Section: Discussionmentioning
confidence: 88%
“…In this study, the rate of resistance to amoxicillinclavulanic acid in E. coli strains was 52%. This rate has been reported to be 33% in elderly patients in the study by Ulug et al [6] and between 6.5% and 32% in the studies consisting of various groups in Turkey [14,15,19,20]. Sanchez et al [18] have found a rate of resistance of 7% against amoxicillin-clavulanic acid in E. coli strains in elderly patients.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations